Live Load Distribution Factor at the Piers of Skewed Continuous Multicell Box Girder Bridges Subjected to Moving Loads. Issue 1 (January 2015) - Mohseni, Iman; Khalim, A. R.; Kang, Junsuk
The multicell box girder bridge is a popular choice of designers because of its large torsional stiffness. The skewness at the support line of bridges has a significant influence on distribution of live loads. The current American bridge design code, AASHTO load and resistance factor design (LRFD), defines several correction factor expressions to account for the skew effect in bridges. In addition, the effect of skewness on reactions of continuous multicell box girder bridges is obtained by using the skew correction factor of shear or by the shear distribution factor of straight bridges, despite a significant disparity between the shear and reaction that is observed in skewed bridges. This study investigated the effect of skewness on the reactions and shear distribution factors for three continuous multicell box girder bridges. There was a significant difference between reactions at the piers and the shear distribution factors of skewed bridges. Thus, a statistical analysis was used to propose new equations for the skew correction factors and the external girder correction factor of shear and reaction to improve the accuracy of the AASHTO LRFD specifications.